USING OF FACTOR ANALYSIS FOR PROGNOSTICATION DISTRIBUTION OF CONTAMINATION UNDERGROUND WATER - CHOMKO, D.; CHOMKO, F. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The proposed new method is the determination of the dependence on the chemical composition’s formation of the underground water from the different natural factors (atmospheric precipitation, rivers and others) and the technogen ones (building, rubbish-heaps and so on). The method is based on the employment of the factor analysis. The employment of that method makes it possible to determine the sources of the underground water pollution. It is tested by the water intake in Novyi Urengol.